Optimalisasi Kinerja Karyawan Bagian Produksi PT. XYZ Kabupaten Majalengka Melalui Motivasi Kerja dan Pembinaan Disiplin - Sukmana, Fakhriji Teja; Romi, Mochamad Vrans (Universitas Batanghari, 2024)
From the data obtained there are several employees whose performance is still lacking in the production section of PT. XYZ Kabupaten Majalengka. . The factors that influence whether employee performance is good or bad are work motivation and discipline development. This research aims to determine the relationship between work motivation and discipline development on the performance of employees in the production department of PT. XYZ Kabupaten Majalengka. The method in this research uses a quantitative method, Â sampling technique namely probability sampling with a simple random sampling type. Data collection techniques include distributing questionnaires and interviews. The data analysis technique uses descriptive methods and associative methods as well as data analysis, namely multiple regression analysis by interpreting the SPSS version 25 program output table. The research results show that work motivation partially influences employee performance, and discipline training not partially influences employee performance. Furthermore, work motivation and discipline development simultaneously influence the performance of production employees. PT. XYZ Kabupaten Majalengka.